CRIMINAL RESPONSIBILITY OF CHILDREN FOR THE PHENOMENON OF MOTORBIKE GANGS IN MAKASSAR - M. Susilo Ihlasul Ashar; Syamsuddin Muchtar (JCH (Jurnal Cendekia Hukum), 2026)
The phenomenon of motorcycle gangs involving children in Makassar City shows an increase in violent crimes, such as bowing, assault, abuse, and the use of sharp weapons, thus raising issues regarding the limits of criminal liability for children from the perspective of Indonesian criminal law. This condition creates a dilemma because on the one hand, children receive protection through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), while on the other hand, law enforcement must be able to provide protection to the community. This study aims to analyze the criminal liability of children for motorcycle gang crimes and the application of the Juvenile Criminal Justice System in realizing a balance between the protection of children's rights and the interests of law enforcement. The study uses a normative-empirical legal method with a statutory, conceptual, and case approach. Data were obtained through observations at the Makassar City Police Headquarters, analysis of laws and regulations, court decisions, and various relevant literature, then analyzed qualitatively using a descriptive-analytical method. The results of the study indicate that the criminal responsibility of children cannot be based solely on age, but must consider the elements of fault (schuld), the ability to be responsible, the form of participation, the level of intent (dolus), and the level of danger (social harm) caused. The phenomenon of motorcycle gangs in Makassar shows a shift from juvenile delinquency to organized collective crime, so that children who consciously play a role as the main perpetrator or active participant must still be held criminally responsible proportionally. This study also found that the implementation of the SPPA Law needs to be carried out proportionally by considering the level of child involvement, the potential for rehabilitation, and the impact of the crime on society in order to achieve a balance between the protection of children's rights, legal certainty, a sense of justice, and the interests of law enforcement.